2022
DOI: 10.1007/s40747-022-00731-8
|View full text |Cite
|
Sign up to set email alerts
|

Student achievement prediction using deep neural network from multi-source campus data

Abstract: Finding students at high risk of poor academic performance as early as possible plays an important role in improving education quality. To do so, most existing studies have used the traditional machine learning algorithms to predict students’ achievement based on their behavior data, from which behavior features are extracted manually thanks to expert experience and knowledge. However, owing to an increase in the varieties and overall volume of behavioral data, it has become more and more challenging to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…One of the most suitable approaches for analyzing neuroscience mechanisms is using FNNs. [14,15] employ NNs for analysis to evaluate changes and receive feedback on the learning process. It can be concluded that problem-solving skills should be developed using a computerized strategy that incorporates both biological and mathematical NNs, along with a combination of neuroscience concepts such as motivation, emotion, metacognition, working memory, processing speed, execution, and memory, among others.…”
Section: Neural Network and Neuroscience Mechanistic Strategies To Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most suitable approaches for analyzing neuroscience mechanisms is using FNNs. [14,15] employ NNs for analysis to evaluate changes and receive feedback on the learning process. It can be concluded that problem-solving skills should be developed using a computerized strategy that incorporates both biological and mathematical NNs, along with a combination of neuroscience concepts such as motivation, emotion, metacognition, working memory, processing speed, execution, and memory, among others.…”
Section: Neural Network and Neuroscience Mechanistic Strategies To Pr...mentioning
confidence: 99%
“…The complexity of the data source that describes learning necessitates the use of an appropriate structure or architecture for the NN algorithm. In this context, fuzzy NNs (FNNs) were chosen because of their adaptability to a variety of orientations and data sources, as evidenced by several researchers [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The experiment showed that decision trees had the best performance in predicting English scores, and Bayesian algorithms had the best performance in predicting mathematics scores, with an accuracy rate of 87.1% and 83.9%, respectively, and found that there was a certain relationship between mathematics and English scores. Xiaoyong Li et al [5] proposed an end-to-end deep learning model that could automatically extract features from heterogeneous student behavior data to predict learning outcomes. They collected and experimented with daily behavior data from 8228 students, and the experiment showed that the accuracy of this deep learning model in grade prediction was better than traditional machine learning algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…The data set for this research was obtained from Beijing University over 145 days in the spring semester. Using extract, transform, and load (ETL) techniques, 9000 students' campus behaviors (Li et al 2022) were gathered from several databases. Data, time, place, and consumption quantity are the additional four characteristics of consumer behavior.…”
Section: Data Elucidationmentioning
confidence: 99%